Striatal-Enriched Protein Tyrosine Phosphatase in Alzheimer’s Disease - Xu, Jian (2012)
Alzheimer’s disease (AD) is the most common form of dementia among the elderly, affecting millions of people worldwide and representing a substantial economic burden. AD is a progressive disease associated with memory loss and impaired cognitive function. The neuropathology is characterized by cortical accumulation of amyloid plaques and neurofibrillary tangles (NFTs). Amyloid plaques are small, aggregated peptides called beta amyloid (Aβ) and NFTs are aggregates of hyperphosphorylated Tau protein. Because Aβ disrupts multiple intracellular signaling pathways, resulting in some of the clinical symptoms of AD, understanding the underlying molecular mechanisms has implications for the diagnosis and treatment of AD. Recent studies have demonstrated that Aβ regulates striatal-enriched protein tyrosine phosphatase (STEP) (PTPN5). Aβ accumulation is associated with increases in STEP levels and activity that in turn disrupts glutamate receptor trafficking to and from the neuronal membrane. These findings indicate that modulating STEP levels or inhibiting its activity may have beneficial effects for patients with AD, making it an important target for drug discovery. This article reviews the biology of STEP and its role in AD as well as the potential clinical applications.